Reconstructive surgeries in the case of the knee joint osteoarthritis - Popsuishapka, Olexii; Lytvyshko, Valerii; Pidgaiska, Olga; Ashukina, Nataliya; Romanenko, Kostiantyn; Danуshchuk, Zinaida (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To clarify the indications and volume of reconstructive surgeries under conditions of knee joint arthritis and to improve the methods of surgical correction of peri-articular deformations using an external rod fixator. Methods. During the last 10 years (2012‒2022), reconstructive surgeries were performed in 45 patients (49 joints). Indications for surgery were based on the study of pain and its localization, peri-articular deformation of the limb, ultrasound (USD) and X-ray examinations. Results. Indications for certain reconstructive surgical interventions on the knee joint are substantiated. The role of pathological changes of the meniscus in the development of knee joint arthritis has been determined. The positive clinical effect of paracapsular resection of the front part of the meniscus with hyperplastic growths of synovial tissue is shown. Deformation of the extremety (43 patients — with varus deformity, 2 — with valgus deformity) limited the function of the limb and caused pain. Surgical treatment in such cases were aimed at eliminating the deformation of the proximal part of the tibia. The types of osteotomies, the features of the author's rod external fixation device application, and the postoperative management of patients are presented. Due to external fixator, it is possible to perform, if necessary, angular correction of the limb axis during the period when the patient begins to walk with partial weight bearing, and the functional load of the limb makes it possible to achieve fusion of fragments within 3.5–4 months. A long-term positive clinical effect was obtained in 42 (93 %) patients. Conclusions. Indications for pathogenetic treatment should be based, first of all, on the identification of the source (or pathogenesis) of the pain syndrome, then on the analysis of the type and magnitude of peri-articular deformation of the limb, signs of functional insufficiency of the limb associated with it. In the third place, the X-ray signs should be analyzed. Elimination of angular peri-articular deformation of the limb has a positive effect on the course of knee arthritis, reduces pain, increases physical activity, and slows down the progression of cartilage destruction.